تأثير تكنولوجيا الإتصال الحديثة على الإتصال الأسري - ضيف، عمر. عبد اللاوي، فارس (جامعة الوادي university of Eloued, 2017)
Abstract: This study aims to highlight the effects of modern communication technology on family communication. The study included a main question: Has modern communication technology affected family communication? From this main question, two questions arise: 1.What are the forms of communication within the family in the valley? 2. Has the Internet changed the form of contact within the family in the valley? The descriptive approach was used to identify the communication within the family and to identify the change caused by modern communication technology, especially the Internet within the family. The sample included 48 families represented in 144 members of the royal family of the internet line in Al Kawthar district. The sample was chosen intentionally, Results: -Despite the use of the sample of the Internet, but this did not change their contact with their families and the duration of sitting with them. - The form of communication and dialogue within the family has not changed significantly under the use of the Internet.
دراسة ميدانية على مجموعة من الأسر من مستخدمي الأنترنت بحي الكوثر ببلدية الوادي
مذكرة ماستر علوم اجتماعية علم اجتماع الإتصال
Keywords: تكنولوجيا الإتصال الحديثة، الأسرة; Technologie de communication moderne, famille; Modern Communication Technology, Family